Hamka’s Reformist Epistemology: Modernist Genealogies, Hermeneutical Strategies, and the Making of Islamic Renewal in the Malay-Indonesian World - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2025)
This study investigates Hamka’s reformist epistemology by examining the modernist genealogies and hermeneutical strategies that shaped his intellectual project in the Malay Indonesian world. While previous scholarship has highlighted Hamka as a literary figure, nationalist thinker, or religious leader, limited attention has been given to the systematic ways in which he internalized, adapted, and transformed the rational modernism of Muhammad Abduh into a distinct framework of Islamic renewal. Addressing this gap, the study aims to identify the intellectual transmission of Abduh’s ideas into Hamka’s corpus, analyze the interpretive principles embedded in Tafsir al Azhar and related writings, and explain how these principles contributed to the emergence of a localized yet cosmopolitan modernist discourse. Methodologically, the research employs qualitative textual analysis, intellectual genealogy, and historical contextualization using primary sources from Hamka’s tafsir, essays, speeches, and archival materials, complemented by secondary analyses of Southeast Asian reform movements. The findings reveal that Hamka developed a reformist epistemology grounded in rational inquiry, ethical intentionality, and the rejection of uncritical conformity, while simultaneously constructing a vernacularized model of Islamic modernity attuned to Malay Indonesian socio cultural realities. This synthesis produced a transformative religious discourse that reshaped educational, doctrinal, and public life across the region. The study contributes theoretically by repositioning Hamka within the global trajectory of Islamic modernism and demonstrating how peripheral intellectual spaces generate original models of reform. Its implications extend to contemporary debates on Islamic hermeneutics, religious authority, and the ongoing negotiation of modernity in Muslim Southeast Asia.